Pengaruh Good Corporate Governance dan Tri Hita Karana terhadap Kijeria LPD di Masa Pandemi Covid-19 pada LPD di Kecamatan Mendoyo Jembrana - Lestari, Ni Ketut Nita; F.Yudiaatmaja (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to examine the effect of GCG and tri hita karana on LPD performance during the covid-19 pandemic at LPDs in Mendoyo, Jembrana District. The research design used in this study is causal quantitative. The subject of this research is LPD Mendoyo Jembrana District and the object of this research is GCG, tri hita karana and LPD performance. Data were collected by questionnaire, document recording and multiple linier regression. The sample in this test is 38 respondents. The result showed that (1) good corporate governace and tri hita karana had a significant effect on LPD performance, (2) GCG had a positive and significant effect on LPD performance, (3) Tri hita karana had a positive and significant effect on LPD performance during the pandemic covid-19 on LPD in Mendoyo Jembrana District